Measuring Bullying in Russian Schools: Prevalence, Age and Gender Correlates, and Associations with School Climate - Maria Novikova; Arthur Rean; Ivan Konovalov (Voprosy obrazovaniya / Educational Studies Moscow, 2021)
This article describes the process of developing instruments to measure school bullying and school climate characteristics as well as presents the results of their evaluation on a sample of 871 middle- and high-school students from a Russian megalopolis. It is shown that bullying prevalence depends on the type of aggressive behavior and involvement, varying from 4% (involvement in physical bullying as a victim or perpetrator) to 45% (involvement in verbal bullying as a bystander). Most often, students get involved in bullying as witnesses, but the number of victims and bullies is not significantly lower. On average, 28% of school students initiate bullying and 33% get bullied once or twice a month. Occasional bullying is more typical of girls, while boys are more likely to bully their peers frequently. Middle-school students (seventh and eighth grades) are at the highest risk of being exposed to bullying in all roles. Four aspects of school climate are also analyzed, all of them being significantly negatively related to bullying involvement (regardless of the type of bullying or respondent’s role in a bullying incident).